Development of a vaccine based on bacteria‐mimicking tumor cells coated with novel engineered toll‐like receptor 2 ligands. Issue 5 (22nd April 2018) - Akazawa, Takashi; Ohashi, Toshimitsu; Wijewardana, Viskam; Sugiura, Kikuya; Inoue, Norimitsu
Abstract : For a successful tumor vaccine, it is necessary to develop effective immuno‐adjuvants and identify specific tumor antigens. Tumor cells obtained from surgical or biopsy tissues are a good source of tumor antigens but, unlike bacteria, they do not induce strong immune responses. Here, we designed 2 novel lipopeptides that coat tumor cell surfaces and mimic bacterial components. Tumor cells coated with these lipopeptides (called bacteria‐mimicking tumor cells [BMTC]) were prepared and their efficacy as a tumor vaccine examined. Natural bacterial lipopeptides act as ligands for toll‐like receptor 2 (TLR2) and activate dendritic cells (DC). To increase the affinity of the developed lipopeptides for the negatively charged plasma membrane, a cationic polypeptide was connected to Pam2Cys (P2C), which is the basic structure of the TLR2 ligand. This increased the non‐specific binding affinity of the peptides for the cell surface. Two such lipopeptides, P2CSK11 (containing 1 serine and 11 lysine residues) and P2CSR11 (containing 1 serine and 11 arginine residues) bound to irradiated tumor cells via the long cationic polypeptides more efficiently than the natural lipopeptide MALP2 (P2C‐GNNDESNISFKEK) or a synthetic lipopeptide P2CSK4 (a short cationic polypeptide containing 1 serine and 4 lysines). BMTC coated with P2CSR11 or P2CSK11 were efficiently phagocytosed by DC and induced antigen cross‐presentation in vitro. They also induced effective tumor‐specific cytotoxic T cell responses and inhibited tumor growth in in vivo mouse models. P2CSR11 activated DC but induced less inflammation‐inducing cytokines/interferons than other lipopeptides. Thus, P2CSR11 is a strong candidate antigen‐specific immuno‐adjuvant, with few adverse effects. Abstract : We designed two novel lipopeptides as anti‐tumor immunoadjuvants that can coat tumor cell surfaces. Tumor cells coated with these engineered lipopeptides (called bacteria‐mimicking tumor cells) promoted DC phagocytosis and antigen cross‐presentation via TLR2 and induced the strong anti‐tumor effect.